Pengaruh Manajemen Usaha Melalui Kualitas Pelayanan, Harga dan Promosi terhadap Keputusan Pembelian - Nursasi, Enggar; Palgoena, Gede Ergha; Bawazier, Muniroh Said (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
The purpose of this study was to partially analyze the effect of service quality, price and promotion on purchasing decisions at the Choco Story Store, Purwoharjo District. The method used is descriptive quantitative research. The sample is 96 respondents. The results of the study obtained that service quality has a positive and significant influence on purchasing decisions at the Choco Story shop. price has a positive and significant influence on purchasing decisions at the choco story shop, promotions have a positive and significant influence on purchasing decisions at the choco story shop.